Use of residues of the dairy industry as a fertilizer for spring wheat. Issue 1 (November 2020) - Vasilyev, O; Vasilyev, A; Nursov, I; Ivanov, YU; Ilyin, A; Terentyeva, M
Abstract: The article presents the results of scientific research on the use of residues of the dairy industry (cake) as an organic fertilizer for spring wheat. Cake refers to the residues obtained by cleaning milk pipes, and has a chemical composition and physical properties similar to cottage cheese, but has a pungent and unpleasant smell of spoiled foods. The direct effect of oilcake on the growth and development of spring wheat on light gray forest loamy soil was studied in field experiments established in 2017–2019. Scientific studies have shown that cake is an excellent organic fertilizer, and its use in doses of 30, 60 and 90 t/ha dramatically increases soil fertility and productivity of spring wheat, improves grain quality.